Post genome-wide association studies of novel genes associated with type 2 diabetes show gene-gene interaction and high predictive value. - Stéphane Cauchi; David Meyre; Emmanuelle Durand; Christine Proença; Michel Marre; Samy Hadjadj; Hélène Choquet; Franck De Graeve; Stefan Gaget; Frederic Allegaert; Jérôme Delplanque; Marshall Alan Permutt; et al. (PLoS ONE)
Background Recently, several Genome Wide Association (GWA) studies in populations of European descent have identified and validated novel single nucleotide polymorphisms (SNPs), highly associated with type 2 diabetes (T2D). Our aims were to validate these markers in other European and non-European populations, then to assess their combined effect in a large French study comparing T2D and normal glucose tolerant (NGT) individuals. Methodology/principal findings In the same French population analyzed in our previous GWA study (3,295 T2D and 3,595 NGT), strong associations with T2D were found for CDKAL1 (OR(rs7756992) = 1.30[1.19-1.42], P = 2.3x10(-9)), CDKN2A/2B (OR(rs10811661) = 0.74[0.66-0.82], P = 3.5x10(-8)) and more modestly for IGFBP2 (OR(rs1470579) = 1.17[1.07-1.27], P = 0.0003) SNPs. These results were replicated in both Israeli Ashkenazi (577 T2D and 552 NGT) and Austrian (504 T2D and 753 NGT) populations (except for CDKAL1) but not in the Moroccan population (521 T2D and 423 NGT). In the overall group of French subjects (4,232 T2D and 4,595 NGT), IGFBP2 and CXCR4 synergistically interacted with (LOC38776, SLC30A8, HHEX) and (NGN3, CDKN2A/2B), respectively, encoding for proteins presumably regulating pancreatic endocrine cell development and function. The T2D risk increased strongly when risk alleles, including the previously discovered T2D-associated TCF7L2 rs7903146 SNP, were combined (8.68-fold for the 14% of French individuals carrying 18 to 30 risk alleles with an allelic OR of 1.24). With an area under the ROC curve of 0.86, only 15 novel loci were necessary to discriminate French individuals susceptible to develop T2D. Conclusions/significance In addition to TCF7L2, SLC30A8 and HHEX, initially identified by the French GWA scan, CDKAL1, IGFBP2 and CDKN2A/2B strongly associate with T2D in French individuals, and mostly in populations of Central European descent but not in Moroccan subjects. Genes expressed in the pancreas interact together and their combined effect dramatically increases the risk for T2D, opening avenues for the development of genetic prediction tests.